Generation of mesenchymal stromal cells from urine-derived iPSCs of pediatric brain tumor patients - Baliña-Sánchez, Carmen; Aguilera, Yolanda; Adán, Norma; Sierra-Párraga, Jesús María; Olmedo-Moreno, Laura; Panadero-Morón, Concepción; Cabello-Laureano, Rosa; Márquez-Vega, Catalina; Martín-Montalvo, Alejandro; Capilla-González, Vivian (Frontiers in Immunology, 2023)
Human induced pluripotent stem cells (iPSCs) provide a virtually inexhaustible source of starting material for next generation cell therapies, offering new opportunities for regenerative medicine. Among different cell sources for the generation of iPSC, urine cells are clinically relevant since these cells can be repeatedly obtained by non-invasive methods from patients of any age and health condition. These attributes encourage patients to participate in preclinical and clinical research. In particular, the use of urine-derived iPSC products is a convenient strategy for children with brain tumors, which are medically fragile patients. Here, we investigate the feasibility of using urine samples as a source of somatic cells to generate iPSC lines from pediatric patients with brain tumors (BT-iPSC). Urinary epithelial cells were isolated and reprogrammed using non-integrative Sendai virus vectors harboring the Yamanaka factors KLF4, OCT3/4, SOX2 and CMYC. After reprogramming, BT-iPSC lines were subject to quality assessment and were compared to iPSCs obtained from urine samples of non-tumor pediatric patients (nonT-iPSC). We demonstrated that iPSCs can be successfully derived from a small volume of urine obtained from pediatric patients. Importantly, we showed that BT-iPSCs are equivalent to nonT-iPSCs in terms of morphology, pluripotency, and differentiation capacity into the three germ layers. In addition, both BT-iPSCs and nonT-iPSCs efficiently differentiated into functional mesenchymal stem/stromal cells (iMSC) with immunomodulatory properties. Therefore, this study provides an attractive approach to non-invasively generate personalized iMSCs products intended for the treatment of children with brain tumors.